Application of the finite element method as assistance to the project and commissioning of electrical grounding systems - Rooney Ribeiro Albuquerque Coelho (2015)
The main aim of this work is to apply the finite element method (FEM), modeled in short circuit current conduction problems at industrial frequency, calculating grounding resistance and verifying whether a particular project is within the safety specifications. The work optimization techniques for soil modeling are used and the FEM is applied as a way to aid substation commissioning, simulating the Fall of Potential method (FOP) as well as step and touch potential experimenting. The research presents the optimal model of soil found by the minimization of the error between the apparent resistivity curve extracted from electrical soil resistivity measurements. The method of Wenner and a theoretical curve of apparent resistivity for a model of "N" horizontal layers is used as well as the algorithm Particle Swarm Optimization (PSO); a fairly consolidated optimization, a metaheuristic, which recorded an excellent performance when applied to a solution of this problem. Various soil stratification were performed using optimization techniques, and the results of case studies that use graph method, extracted from literature were confronted with this method. The model of grounding problems using the FEM was presented as an alternative solution to the project using the IEEE Std 80, being possible to determine the spatial distribution of the electric potential at all points of the soil, which was modeled as heterogeneous, so getting to know the regions of the project which have the highest potential levels of step and touch. The FEM was also applied to determine the exact location of potential probe in the ground resistance measurement test which was validated through field experiments and through results extracted from literature. The method was also applied to the determination of the potential levels of step and touch existing in a substation, being the testing simulated and proven through field experiments.